The Influence of Product Quality, Price, and Service on Customer Satisfaction and Loyalty at Goodtry Burger Outlets Using SEM-PLS - Mardiyanto, Joko; Heikal, Jerry (Jurnal Indonesia Sosial Sains, 2025)
This study aims to examine the influence of product quality, price, and service on customer satisfaction and customer loyalty at GOODTRY burger outlets using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The research investigations five key variables: product quality, price, service, customer satisfaction, and customer loyalty. Data were collected from 46 respondents through an online questionnaire distributed to active customers. The results show that price and service significantly affect customer satisfaction, with coefficients of 0.306 (p = 0.029) and 0.349 (p = 0.018), respectively. Additionally, price has a strong and significant impact on customer loyalty (coefficient = 0.570, p = 0.000). In contrast, product quality does not have a statistically significant effect on either satisfaction (p = 0.077) or loyalty (p = 0.369), and service has no significant direct effect on loyalty (p = 0.057). These findings highlights the critical role of pricing strategies and service quality in fostering customer satisfaction and loyalty in the fast-food sector.